The phytochemical epigallocatechin gallate prolongs the lifespan by improving lipid metabolism, reducing inflammation and oxidative stress in high‐fat diet‐fed obese rats. Issue 9 (30th July 2020) - Yuan, Hang; Li, Yuqiao; Ling, Fan; Guan, Yue; Zhang, Dandan; Zhu, Qiushuang; Liu, Jinxiao; Wu, Yuqing; Niu, Yucun
Abstract: We have recently reported that epigallocatechin gallate (EGCG) could extend lifespan in healthy rats. This study aimed to investigate the effects and mechanisms of a high dose of EGCG in extending the lifespan of obese rats. Ninety adult male Wistar rats were randomly divided into the control (NC), high‐fat (HF) and EGCG groups. Serum glucose and lipids, inflammation and oxidative stress were dynamically determined from adulthood to death, and the transcriptome and proteome of the liver were also examined. The median lifespans of the NC, HF and EGCG groups were 693, 599 and 683 days, respectively, and EGCG delayed death by 84 days in obese rats. EGCG improved serum glucose and lipids and reduced inflammation and oxidative stress associated with aging in obese rats induced by a high‐fat diet. EGCG also significantly decreased the levels of total free fatty acids (FFAs), SFAs and the n‐6/n‐3 ratio but significantly increased the n‐3 FFAs related to longevity. The joint study of the transcriptome and proteome in liver found that EGCG exerted its effects mainly by regulating the suppression of hydrogen peroxide and oxygen species metabolism, suppression of oxidative stress, activation of fatty acid transport and oxidation and cholesterol metabolism. EGCG significantly increased the protein expression of FOXO1, Sirt1, CAT, FABP1, GSTA2, ACSL1 and CPT2 but significantly decreased NF‐κB, ACC1 and FAS protein levels in the livers of rats. All the results indicate that EGCG extends lifespan by improving FFA metabolism and reducing the levels of inflammatory and oxidative stress in obese rats. Abstract : This study investigates the effects and mechanisms of a high dose of epigallocatechin gallate (EGCG) in extending the lifespan of obese rats. We find that EGCG improved serum glucose, lipids, inflammation, oxidative stress associated with ageing in obese rats induced by a high‐fat diet, total free fatty acids (FFAs), transcriptome, and proteome. The results indicate that EGCG extends lifespan by improving FFA metabolism and reducing the levels of inflammatory and oxidative stress in obese rats.